Peningkatan Kualitas dan Kapasitas Produk Olahan Berbasis Perikanan Laut dengan Teknologi Tepat Guna - Mutiara Nugraheni; Titin Hera Widi Handayani; Agung Utama; Arif Marwanto (Universitas Lancang Kuning, 2021)
This community service aims to solve the problems faced by the Mina Bahari 45 group related to the quality and production capacity to support product marketing. The activities done were to carry out the appropriate technology transfer activities and the strengthening of marketing that is strengthening the quality and capacity of processed products based on sea fisheries, strengthening production management; renovation and re-lay out the product display. The results of community service related to strengthening production management are the selection and handling of raw materials, processing and packaging. Operationalization of automatic cracker frying Machine and industrial scale steamer as well as renovation and re-lay out display place to support off-line marketing in Depok Beach. The use of appropriate technology can increase production capacity at least by 15% and improve the quality of products produced that include texture, shape and color and the availability of a product display space that is safe for products, attractive and adequate.